2020
DOI: 10.1097/rti.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Chest Computed Tomography in Differentiating Coronavirus Disease 2019 From Other Viral Infections Using a Standardized Classification

Abstract: Background: An expert consensus recently proposed a standardized coronavirus disease 2019 (COVID-19) reporting language for computed tomography (CT) findings of COVID-19 pneumonia. Purpose: The purpose of the study was to evaluate the performance of CT in differentiating COVID-19 from other viral infections using a standardized reporting classification. Methods: A total of 175 consecutive patients were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…They also revealed that PPV of “typical appearance” was 40.0% at a prevalence of 16.7% and increased to 87.8% at 46.4% [ 61 ]. Similar trends were observed in reports from other countries, i.e., Brazil [ 60 , 63 , 66 , 67 ], Japan [ 49 ], and USA [ 64 ] and other institutions in Italy [ 61 , 62 , 65 ]. Regarding the diagnostic performance against other viral pneumonias, a retrospective cohort study from Brazil reported similar results with a sensitivity and specificity of 73.6% and 97.7%, respectively, for “typical appearance” [ 65 ].…”
Section: Performance Of Rsna Classificationsupporting
confidence: 87%
See 2 more Smart Citations
“…They also revealed that PPV of “typical appearance” was 40.0% at a prevalence of 16.7% and increased to 87.8% at 46.4% [ 61 ]. Similar trends were observed in reports from other countries, i.e., Brazil [ 60 , 63 , 66 , 67 ], Japan [ 49 ], and USA [ 64 ] and other institutions in Italy [ 61 , 62 , 65 ]. Regarding the diagnostic performance against other viral pneumonias, a retrospective cohort study from Brazil reported similar results with a sensitivity and specificity of 73.6% and 97.7%, respectively, for “typical appearance” [ 65 ].…”
Section: Performance Of Rsna Classificationsupporting
confidence: 87%
“…Regarding the diagnostic performance against other viral pneumonias, a retrospective cohort study from Brazil reported similar results with a sensitivity and specificity of 73.6% and 97.7%, respectively, for “typical appearance” [ 65 ]. They also evaluated the CT classification in relation to the duration of symptoms, which showed that “indeterminate appearance” and “negative for pneumonia” were significantly more frequent in patients with symptom duration of 0–5 days than > 5 days, suggesting milder CT patterns in the early stage of infection [ 66 ]. A retrospective cohort study from Italy that compared the diagnostic performance in relation to age reported that PPV, NPV, and accuracy were not statistically different among the different age groups in their study comprising patients > 60, ≥ 50 and < 60, or < 50 [ 62 ].…”
Section: Performance Of Rsna Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teles et al. reported a high specificity and positive predictive value for standardized chest CT classification ( 18 ) . Conduction of randomized controlled studies seems imperative to settle the issue.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding was that more than half of the respondents who had predominantly used CXR indicated that they would have preferred to use chest CT to assess/exclude COVID-19 pneumonia. The desire to change the diagnostic method from CXR to chest CT is likely due to the relatively higher sensitivity of chest CT in the detection of lung abnormalities (especially in the early stage of the disease) [ 13 20 ], as well as its superior ability to differentiate COVID-19 pneumonia from other infectious and noninfectious interstitial diseases [ 38 40 ]. However, CXR does have several advantages in the management of patients with suspected or confirmed COVID-19 infection [ 6 13 ].…”
Section: Discussionmentioning
confidence: 99%